Validation of acute myocardial infarction in the Food and Drug Administration's Mini‐Sentinel program. (29th June 2012) - Cutrona, Sarah L.; Toh, Sengwee; Iyer, Aarthi; Foy, Sarah; Daniel, Gregory W.; Nair, Vinit P.; Ng, Daniel; Butler, Melissa G.; Boudreau, Denise; Forrow, Susan; Goldberg, Robert; Gore, Joel; et al.
ABSTRACT Purpose To validate an algorithm based upon International Classification of Diseases, 9th revision, Clinical Modification (ICD‐9‐CM) codes for acute myocardial infarction (AMI) documented within the Mini‐Sentinel Distributed Database (MSDD). Methods Using an ICD‐9‐CM‐based algorithm (hospitalized patients with 410.x0 or 410.x1 in primary position), we identified a random sample of potential cases of AMI in 2009 from four Data Partners participating in the Mini‐Sentinel Program. Cardiologist reviewers used information abstracted from hospital records to assess the likelihood of an AMI diagnosis based on criteria from the Joint European Society of Cardiology and American College of Cardiology Global Task Force. Positive predictive values (PPVs) of the ICD‐9‐based algorithm were calculated. Results Of the 153 potential cases of AMI identified, hospital records for 143 (93%) were retrieved and abstracted. Overall, the PPV was 86.0% (95% confidence interval; 79.2%, 91.2%). PPVs ranged from 76.3% to 94.3% across the four Data Partners. Conclusions The overall PPV of potential AMI cases, as identified using an ICD‐9‐CM‐based algorithm, may be acceptable for safety surveillance; however, PPVs do vary across Data Partners. This validation effort provides a contemporary estimate of the reliability of this algorithm for use in future surveillance efforts conducted using the Food and Drug Administration's MSDD. Copyright © 2012 John Wiley & Sons, Ltd.